Implementation of Content Based Filtering Method in Restaurant Menu Ordering Recommendation System - Anang Pramono; Timotius Satrio Setyo Ardi Wolayan (Return : Study of Management, Economic and Bussines, 2024)
Sales is one of the key factors in business. Failure to increase sales can lead to the collapse and bankruptcy of a business. Recommendation System is a system that is capable of predicting products desired by users. Personalized product recommendations effectively boost sales in a business. In this context, the recommendation system is a strategic tool to optimize the user experience and encourage further purchases. This research applies the content-based filtering method, which utilizes an item similarity-based recommendation approach. Three variables are used to determine the recommended product order: similarity value, sales quantity, and rating. Based on the trial, it was found that 77.3% of users were interested in the recommended products, while the remaining 22.7% preferred to purchase other products. Therefore, it can be concluded that the recommendation system can influence users to purchase the recommended products, thus impacting sales.